The Servant: A Simple Story About the True Essence of Leadership - Hunter, James C (Prima Connunications, Inc, 1998)
In this absorbing tale, you watch the timeless principles of servant leadership unfold through the story of John Daily, a businessman whose outwardly successful life is spiraling out of control. He is failing miserably in each of his leadership roles as boss, husband, father, and coach. To get his life back on track, he reluctantly attends a weeklong leadership retreat at a remote Benedictine monastery. To John's surprise, the monk leading the seminar is a former business executive and Wall Street legend. Taking John under his wing, the monk guides him to a realization that is simple yet profound: The true foundation of leadership is not power, but authority, which is built upon relationships, love, service, and sacrifice. Along with John, you will learn that the principles in this book are neither new nor complex. They don't demand special talents; they are simply based on strengthening the bonds of respect, responsibility, and caring with the people around you. Perhaps this is why The Servant has touched readers from all walks of life$1 (Bbecause its message can be applied by anyone, anywhere$1 (Bat home or at work. If you are tired of books that lecture instead of teach; if you are searching for ways to improve your leadership skills; if you want to understand the timeless virtues that lead to lasting and meaningful success, then this book is one you cannot afford to miss.s
Keywords: Business & Economics; Management